Religious liberties - Fenton, Elizabeth A. (Oxford University Press, 2011)
Early U.S. literary & cultural productions often presented Catholicism as a threat not only to Protestantism but also to democracy. Religious Liberties shows that U.S. understandings of religious freedom & pluralism emerged, paradoxically, out of a virulent anti-Catholicism.
10.1093/acprof:oso/9780195384093.001.0001
Keywords: American literature; Cultural pluralism in literature; Anti-Catholicism in literature; Religion and literature; Liberalism in literature; Democracy in literature